COVID‐19 (Omicron strain) hospital admissions from a virtual ward – who required further care?. Issue 3 (26th March 2023) - Mackay, Ian; France, Megan; McAuley, Duncan; Wing, Sean; Wheeldon, Mary; Britton, Susan; Todd, Catherine; Pitiris, Alexandra; Barrett‐Beck, Leah; Rushbrook, Elizabeth; Bennett, Cameron; McCarthy, Kate
Abstract: Background: The COVID‐19 virtual ward was created to provide care for people at home with COVID‐19. Given this was a new model of care, little was known about the clinical characteristics and outcomes of patients requiring admission to hospital from the virtual ward platform. The aims were to characterise hospital admission volume, patient epidemiology, clinical characteristics, and outcome from a virtual ward in the setting of an Omicron (BA.1, BA.2) outbreak. Methods: A retrospective observational study was performed for all virtual ward patients admitted from 1st January 2022 to 25th March 2022 (over 16 years old). Epidemiological, clinical and laboratory data was reviewed on all patients who required hospital admission. Results: A total of 7021 patients were cared for on the virtual ward over the study period with 473 referred to hospital for assessment. Twenty‐six (0.4%) patients were admitted to hospital during their care on the ward. Twenty‐two (84.6%) admissions were COVID‐19 related. Fifty three percent of the hospitalised patients were fully vaccinated and 11 had received prior therapeutics for COVID‐19. Shortness of breath was the most common reason for escalation to hospital. Chest pain was the second most common reason and the most common diagnosis after investigation was non‐cardiac chest pain. Conclusions: Few patients required admission from the virtual ward in the setting of the Omicron variant (BA.1, BA.2) as a direct result of COVID‐19 disease and virtual ward care. Shortness of breath and chest pain were the most common symptoms driving further clinical care.